Feminization and Labor Vulnerability in Global Manufacturing Industries: Does Gendered Discourse Matter?. Issue 3 (1st October 2013) - Hossain, Md. Ismail; Mathbor, Golam M.; Semenza, Renata
<x xml:space="preserve">Abstract</x> Two contested arguments persist in explaining the causes of feminization and labor vulnerability. Some scholars argue that global industries are dominated by female workers as a result of the search for cheap labor. On the other hand, some scholars claim that the primary cause of feminization and labor vulnerability is the gendered discourses of work. Drawing views from readymade garment (RMG) industries of Bangladesh, this paper argues that both economic choices of cheap labor and gendered discourses of work collaboratively contribute to feminizing the labor force. This feminization of the workforce enables the violation of labor rights and benefits capitalists.